Chimeric Mice Engrafted With Canine Hepatocytes Exhibits Similar AAV Transduction Efficiency to Hemophilia B Dog - Shao, Wenwei; Sun, Junjiang; Chen, Xiaojing; Dobbins, Amanda; Merricks, Elizabeth P.; Samulski, R. Jude; Nichols, Timothy C.; Li, Chengwen (Frontiers in Pharmacology, 2022)
Adeno-associated virus (AAV) mediated gene therapy has been successfully applied in clinical trials, including hemophilia. Novel AAV vectors have been developed with enhanced transduction and specific tissue tropism. Considering the difference in efficacy of AAV transduction between animal models and patients, the chimeric xenograft mouse model with human hepatocytes has unique advantages of studying AAV transduction efficiency in human hepatocytes. However, it is unclear whether the results in humanized mice can predict AAV transduction efficiency in human hepatocytes. To address this issue, we studied the AAV transduction efficacy in canine hepatocytes in both canine hepatocyte xenografted mice and real dogs. After administration of AAV vectors from different serotypes into canine hepatocyte xenograft mice, AAV8 induced the best canine hepatocyte transduction followed by AAV9, then AAV3, 7, 5 and 2. After administration of AAV/ cFIX (cFIX-opt-R338L) vectors in hemophilia B dogs, consistent with the result in chimeric mice, AAV8 induced the highest cFIX protein expression and function, followed by AAV9 and then AAV2. These results suggest that mice xenografted with hepatocytes from different species could be used to predict the AAV liver transduction in real species and highlight this potential platform to explore novel AAV variants for future clinical applications.